Ruddy Shelduck Tadorna ferruginea home range and habitat use during the non-breeding season in Assam, India - Namgail, Tsewang; Takekawa, John Y; Sivananinthaperumal, Balachandran; Sathiyaselvam, Ponnusamy; Areendran, Gopala; Sathiyaselvam, Ponnusamy; Mundkur, Taej; Mccracken, Tracy; Newman, Scott (Wildfowl, 2013)
India is an important non-breeding ground for migratory waterfowl in the Central Asian Flyway. Millions of birds visit wetlands across the country, yet information on their distribution, abundance, and use of resources is rudimentary at best. Limited information suggests that populations of several species of migratory ducks are declining due to encroachment of wetland habitats largely by agriculture and industry. The development of conservation strategies is stymied by a lack of ecological information on these species. We conducted a preliminary assessment of the home range and habitat use of Ruddy Shelduck Tadorna ferruginea in the northeast Indian state of Assam. Seven Ruddy Shelducks were fitted with solar-powered Global Positioning System (GPS) satellite transmitters, and were tracked on a daily basis during the winter of 2009–2010. Locations from all seven were used to describe habitat use, while locations from four were used to quantify their home range, as the other three had too few locations (< 30) for home range estimation. A Brownian Bridge Movement Model (BBMM), used to estimate home ranges, found that the Ruddy Shelduck had an average core use area (i.e. the contour defining 50% of positions) of 40 km2 (range = 22–87 km2) and an average home range (95% contour) of 610 km2 (range = 222–1,550 km2). Resource Selection Functions (RSF), used to describe habitat use, showed that the birds frequented riverine wetlands more than expected, occurred on grasslands and shrublands in proportion to their availability, and avoided woods and cropland habitats. The core use areas for three individuals (75%) were on the Brahmaputra River, indicating their preference for riverine habitats. Management and protection of riverine habitats and nearby grasslands may benefit conservation efforts for the Ruddy Shelduck and waterfowl species that share these habitats during the non-breeding season.